Multivitamins preventive therapy against subclinical endometritis in buffaloes: Its correlation to NEFA and oxidative stress - Ahmed, Eman A.; Elsayed, Doaa H.; Kilany, Omnia E.; El-Beltagy, Marwa A. (Reproductive biology, 2017)
•Study assesses the preventive effect of AD3E against subclinical endometritis in buffaloes.•Current study highlighted the antioxidant efficacy of AD3E combination.•AD3E combination reduces NEFA level and the incidence of SCE in buffaloes.•Vitamins combination improves the reproductive pattern. The current study was designed to elucidate the in vivo antioxidant, preventive, and ameliorating effects of vitamins AD3E on the incidence of subclinical endometritis (SCE) in buffaloes. Twenty-four buffaloes were divided equally into two groups; group I: control and group II: received AD3E combination. Endometrial cytological samples (n=48) were collected using cytobrush to diagnose SCE by counting polymorphonuclear cells (PMN) ≥6% at 5th (W5) and≥4% at 7th (W7) weeks postpartum. Results revealed that serum superoxide dismutase and nitric oxide significantly increased and decreased, respectively at W7 in AD3E group. The PMN% were significantly correlated with oxidative/anti-oxidative stress markers at W5 and W7. Vaginal score, PMN%, and blood neutrophils were significantly higher in the control group buffaloes than the AD3E enriched ones. Therefore, the prevalence of SCE reduced significantly in the AD3E supplemented buffaloes as compared to the control ones at W5 (23.15% and 38.46%) and W7 (9.8% and 32.34%), respectively. The control group revealed higher NEFA levels (P≤0.05) at W5 and W7 than the AD3E group. The AD3E supplemented buffaloes had shorter days open and higher pregnancy rate at 120th and 150th days postpartum than the control ones. In conclusion, micronutrients (AD3E) intervention acts as a safeguard against the incidence of postpartum SCE and significantly improves the reproductive performance of buffaloes.